2021
DOI: 10.21608/aijpms.2021.54059.1026
|View full text |Cite
|
Sign up to set email alerts
|

Mito-TEMPO improved L-Arginine- induced acute pancreatitis in rats via TLR-4/ NF-кB/ NLRP3 inflammasome downregulation and antioxidant properties

Abstract: Background: Acute pancreatitis (AP) is a globally significant disease with increasing incidence and prevalence especially in the western world. It has severe complications such as pseudocyst, infection, renal failure, breathing problems, diabetes, malnutrition and chronic pancreatitis. Chronic pancreatitis can lead to pancreatic cancer which is one of the worst types of cancer. Up till now, there is no licensed specific treatment for AP. Objective: This study investigated the therapeutic effects of Mito-TEMPO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Observed typical acinar damage and inflammation were confirmed by a serum amylase level elevation (Amy et al, 2014;Ali et al,2020). Fawzy et al, 2021 reported that acute pancreatitis showed inflammation with lobular atrophy, apoptosis and vacuolar degeneration of acinar cells. Non-significant differences in the serum glucose levels were detected in the tested groups in the comparison with the control group due to using of only a single dose of L-arginine that induced mild acute pancreatitis without B cell injury.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Observed typical acinar damage and inflammation were confirmed by a serum amylase level elevation (Amy et al, 2014;Ali et al,2020). Fawzy et al, 2021 reported that acute pancreatitis showed inflammation with lobular atrophy, apoptosis and vacuolar degeneration of acinar cells. Non-significant differences in the serum glucose levels were detected in the tested groups in the comparison with the control group due to using of only a single dose of L-arginine that induced mild acute pancreatitis without B cell injury.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, MDA and NO were elevated in AP, whereas SOD activity and GSH levels were lowered. In addition, Fawzy et al, (2021) discovered that L-arginine promoted AP in rats via increasing serum amylase and lipase levels. The ALT and AST levels were strongly connected with the severity of pancreatitis, and they return to normal when pancreatitis is resolved (Kanwal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%